Peak expiratory flow rate in children aged 6 to 14 years - Gunasekaran, A. (International Journal of Contemporary Pediatrics, 2021)
Background: The objective of this study was to record the PEFR values in children aged between 6 to 14 years. Methods: A cross sectional study was conducted among 1205 children aged 6 to 14 years in department of paediatrics at a medical college hospital. In a pre-structured questionnaire, the age, sex and PEFR values were recorded. PEFR was considered as primary outcome variable. SPSS version 20 was used for data analysis. Results: Total of 1205 children, 51% were boys and 49% were girls. Ninety children of age 6 years ranged between 60 to 200 with 111.1±29.4 and 7 years ranging from 70 to 210 with 136.3±30.5. One hundred and five of age 8 years had 156.9±33.3 ranging from 90 to 230 and 126 of age 10 years with 195.7±38.8 ranging from 110 to 290. Mean PEFR for boys increased with their age and was greater than girls. Conclusions: The overall mean PEFR values for the age group 6 to 14 years was 225±90.07 l/min. Boys have higher PEFR value than girls of the same age group. Hence, PEFR values in this study can be used clinically as reference value for children aged 6 to 14 years.